A Brief Body-Mind-Spirit Group Therapy for Chinese Medicine Stagnation Syndrome: A Randomized Controlled Trial - Siu-man Ng (Evidence-Based Complementary and Alternative Medicine, 2018)
Background. Stagnation syndrome, a diagnostic entity in traditional Chinese medicine (TCM), is characterized by mind-body obstruction-like symptoms. Although TCM has long-established symptom-relief treatments, a comprehensive mind-body intervention was called for. Purpose. The study evaluated the efficacy of a six-session body-mind-spirit (BMS) group therapy for persons with stagnation syndrome. Method. A 2-arm randomized controlled trial design was adopted. The control group received a parallel general TCM instruction course. Both groups completed a pretest (T0), posttest (T1), and 2-month follow-up assessment (T2). The measures included self-report scales on stagnation, depression, anxiety, physical distress, daily functioning, and positive and negative affect; the other measure was of salivary cortisol, a biological marker of stress. Results. Data on 111 adults with stagnation syndrome were included in the analysis. Completion rates were high (over 87%) for both the intervention and control groups. Repeated-measures multivariate MANOVA revealed a significant combined effect with large effect size (eta-squared = 0.42). Repeated-measures ANOVA further revealed that the intervention group showed significant improvements in stagnation, the primary outcome, with medium effect size (eta-squared = 0.11). The intervention group also showed significant improvements in depression, physical distress, everyday functioning, and negative affect (eta-squared = 0.06 to 0.13). Post hoc analysis revealed that the intervention group showed significant improvements over the control group in cortisol level at 2-month follow-up assessment (T0 versus T2) with small effect size (eta-squared = 0.05), but not at posttest (T0 versus T1). Conclusions. Overall, the findings indicate that our brief BMS group therapy intervention for stagnation syndrome is efficacious. Moreover, the intervention resulted in a number of substantial improvements in the physical and mental health domains.